The Outer Membrane Protein OmpW Enhanced V. cholerae Growth in Hypersaline Conditions by Transporting Carnitine - Fu, Xiuping; Zhang, Jingyun; Li, Tianyi; Zhang, Mei; Li, Jie; Kan, Biao (Frontiers in Microbiology, 2018)
Pathogenic marine bacteria are found in environments and food sources with high salt concentrations, which the bacteria must effectively manage for their survival. Several mechanisms, such as the transport of ions and compatible solutes as well as changes in aerobic and anaerobic respiration, confer salt tolerance to bacteria. In this study, we found that the outer membrane protein OmpW was related to salt stress in Vibrio cholerae and that ompW gene transcription and expression were up-regulated in cultures containing high NaCl concentrations. Deletion of ompW resulted in reduced V. cholerae growth in hypersaline culture conditions. Supplements of the compatible solutes betaine, L-carnitine or L-lysine enhanced the growth of V. cholerae in hypersaline media. Supplements of betaine or L-lysine had the same growth enhancement effect on the ompW-deletion mutant cultured in hypersaline media, whereas L-carnitine supplementation did not restore mutant growth. In addition, the uptake of L-carnitine was decreased in the ompW-deletion mutant. Our study showed that among the multiplex factors that enhance the hypersaline tolerance of V. cholerae, OmpW also plays a role by transporting L-carnitine.